Prague in the reign of Rudolph II - Fučíková, Eliška 1940- (The Prague series, 2015)
Prague in the reign of Rudolph II' takes readers back to the days of the Habsburg Emperor Rudolph II (1576-1611) when Prague became the metropolis of the Holy Roman Empire, and when the imperial court was a much sought-after milieu for scholars and artists, as well as magicians and adventurers. As the author notes, almost anyone of importance from inside-and even outside-the empire had to spend some time in Prague if they wanted to make their name. Internationally renowned expert on Rudolphine art Eliska Fucikova provides the reader with an engaging and informative stroll through Rudolphine Prague, which to this day remains full of mystery and legend, and includes a look at the famous imperial collection housed within Prague Castle. Her lively and authoritative account is accompanied by over a hundred color plates of buildings and historic monuments dating from the late Renaissance, together with maps and other graphic documentation, an index of locations with a map of Rudolphine monuments, and an overview of prominent figures.0A follow-up to Karolinum's earlier Art-Nouveau Prague, and the first title in their new Prague series, Prague in the Reign of Rudolph II is sure to be prized by art lovers and adventurers alike